Hypertension as a risk factor for atherosclerosis: Cardiovascular risk assessment - Poznyak, Anastasia V.; Sadykhov, Nikolay K.; Kartuesov, Andrey G.; Borisov, Evgeny E.; Melnichenko, Alexandra A.; Grechko, Andrey V.; Orekhov, Alexander N. (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is a predecessor of numerous cardiovascular diseases, which often lead to morbidity and mortality. Despite the knowledge of atherosclerosis pathogenesis, an essential gap in our understanding is the exact trigger mechanism. A wide range of risk factors have been discovered, however, the majority of them are too general to clarify the launching mechanism of atherogenesis. Some risk factors are permanent (age, gender, genetic heritage), others can be modified (tobacco smoking, physical inactivity, poor nutrition, high blood pressure, type 2 diabetes (T2D), dyslipidemia, obesity). All of them have to be taken into account. In the scope of this review, our attention is focused on hypertension, which is considered the most widespread among all modifiable risk factors for atherosclerosis development. Moreover, high blood pressure is the most investigated risk factor. The purpose of this review is to summarize the data on hypertension as a risk factor for atherosclerosis development and the risk assessment.